Effectiveness of Implementing Principal Leadership Principles Towards Improving the Quality of Administrative Services Education at SMA Negeri Sipora Selatan, Mentawai - Sihotang, Hotmaulina; Samaloisa, Benhur (Universitas Ahmad Dahlan, 2025)
Quality education is the focus of stakeholders, namely school principals, vice principals, teachers, students, parents, and the community. Quality education can be achieved by supporting the school principal's leadership and educational administration services. Background. This study aims to reveal the application of principal leadership principles in improving the quality of educational administration at SMA Negeri 1 Sipora Selatan. Methods. The research approach is qualitative and uses descriptive methods. The data on leadership principle services has been obtained through interviews with school principals, focusing on key managerial tasks, entrepreneurial development, and the supervision of teachers and education staff to develop and enhance the quality of schools. Administrative service data has been obtained through questionnaires. Results. The school principal consistently encourages staff to seek out and implement new strategies in carrying out administrative service tasks. Conclusion. Based on the data obtained, good educational administration services still have room for improvement to reach an even better condition.